Principles of security and trust : 8th International Conference, POST 2019, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings /: 8th International Conference, POST 2019, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings. (2019) - Unknown
No abstract available